Role of the Extracellular Traps in Central Nervous System - Wu, Xinyan; Zeng, Hanhai; Cai, Lingxin; Chen, Gao (Frontiers in Immunology, 2021)
It has been reported that several immune cells can release chromatin and granular proteins into extracellular space in response to the stimulation, forming extracellular traps(ETs). The cells involving in the extracellular traps formation are recognized include neutropils, macrophages, basophils, eosinophils and mast cells. With the development of research related to central nervous system, the role of ETs has been valued in neuroinflammation, blood brain barrier and other fields. Meanwhile, it has been found that microglial cells as the resident immune cells of the central nervous system can also release ETs, updating the original understanding. This review aims to clarify the role of the ETs in central nervous system, especially in neuroinflammation and blood brain barrier.